Reliability and validity of the International Physical Activity Questionnaire Short- Form (IPAQ-sf) in people with COPD - Flora, Sofia Monteiro (2020)
Background: People with chronic obstructive pulmonary disease (COPD) present low levels of physical activity (PA) in daily life and they are advised to undertake as much PA as their health allows. Since PA is crucial to improve COPD prognosis, its assessment and promotion is a priority. The International Physical Activity Questionnaire Short-Form (IPAQ-sf) is widely used for this propose, but there is limited evidence on its clinimetric properties in COPD. Aim: This study aimed to assess the test-retest reliability and validity of the IPAQ-sf in people with COPD. Methods: This prospective cross-sectional non-experimental study assessed the validity of IPAQ-sf in 55 participants using accelerometry (ActiGraph GT3X+) and the test-retest reliability/agreement using the IPAQ-sf results obtained in two different occasions. The period between the two assessments was 7 days, corresponding to the time that participants were using the accelerometer. Test-retest reliability/agreement was assessed with: intraclass correlation coefficient (ICC 95% CI), 95% limits of agreement (95% LoA), standard error of measurement (SEM) and minimal detectable change (MDC95) for continuous variables; and percentage of agreement for categories “physically inactive” vs “physically active” and “low PA”, “moderate PA” and “high PA”. The criterion validity of IPAQ-sf was assessed using Spearman’s correlations (ρ) between results obtained from IPAQ-sf (METSmin/week, time in vigorous and moderate PA and walking) and the accelerometer-based data (total METs-min/week, time in vigorous and moderate PA per week and step counts). For categorical variables was use percentage of agreement and Cohen’s kappa coefficient, as well as sensitivity and specificity.Results: Test-retest reliability of the IPAQ-sf METs-min/week was acceptable (ICC=0.738, 95% CI 0.629 ─ 0.873) but with wide 95% LoA (-5713 ─ 4793.3 METs-min/week). SEM and MDC95 were 1844.7 and 5113.3 METs-min/week, respectively. The agreement among IPAQ-sf categories of PA intensities was 67.3% with moderate weighted Cohen’s kappa of 0.523 (95% CI 0.352 ─ 0.693). The agreement in identifying “physically active” and “physically inactive” patients increase to 85.45% with substantial kappa of 0.660 (95% CI 0.444 ─ 0876). Significant, positive and moderate were found between IPAQ-sf METs-min/week and accelerometer-based data (0.515≤ρ≤0.596), except for time in vigorous PA which has no statistical significance (p>0.05). Agreement between the IPAQ-sf and accelerometer in identifying “physically inactive” and “physically active” patients was 67.3%, with fair Cohen’s kappa of 0.350 (95% CI 0.279 ─ 0.571). The IPAQ-sf presented a high sensitivity (0.89, 95% CI 0.887 ─ 0.891) but a low specificity (0.46, 95% CI 0.46 ─ 0.47). Conclusion: Overall, the present findings seem to suggest that the IPAQ-sf could not be the most appropriate measurement tool in patients with COPD to assess their PA levels.